PEMBERDAYAAN MASYARAKAT PANTAI DAN EDUKASI KESEHATAN GIGI DAN MULUT PADA ANAK-ANAK USIA SEKOLAH DI PASIA NAN TIGO KOTA PADANG - Putri Dafriani; Harinal Afri Resta; Putri Minas Sari (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The low level of public awareness in maintaining oral health is important, because dental and oral diseases can reduce productivity. The high rate of dental caries requires that this problem be introduced early to school age children. The goal of the community service in Pasia Nan Tigo Village is to form health cadres and increase the knowledge of school-age children about oral and dental health. The method used was the empowerment of 5 health cadres, giving educational lectures, counseling, demonstration of tooth brushing skills. The level of knowledge was measured qualitatively by comparing knowledge of dental and oral health before and after health education. The results were obtained, the participants enthusiastically participated in the event from beginning to end. They also provide ideas and suggestions related to dental and oral health problems in the community. After education, the participants can demonstrate the correct brushing technique. Suggestions for the need for government and higher education cooperation to provide enlightenment, solutions to health problems in society.